(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe study is the product of an on-line session with Oregon University. It aimsat developing the students’ attitudes toward using computers in learning to get theadvantages of CALL and autonomous learning. The researcher has depended on aone-group design of a pre-scale and post-scale to measure the effect due to exposureto computer using.